2017
DOI: 10.5210/jbc.v41i1.7314
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Morphogenesis with the Processing Programming Language

Abstract: We used Processing, a visual artists' programming language developed at MIT Media Lab, to IntroductionProcessing is a Java based software language and environment created at MIT Media Laboratory in 2001 for visual modeling (www.processing.org). Processing has grown into a popular tool and online community for programming within the visual arts and data visualization fields. Several artists have used Processing to model or simulate various biological phenomena. One artist animated a matrix of biological cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…3C). Quantitative measurements further showed that control optic axonal arbors had a mean branching angle of 68° (SE = 2.7, n = 91 angles in 10 control GFP arbors; also see Patel et al, 2017). However, for APCNTERM optic axonal arbors, we measured an average bifurcation angle of 75° (SE =2.9, 93 angles in 16 APCNTERM arbors).…”
Section: Apcnterm Expressing Optic Axonal Arbors Have Increased Bifurmentioning
confidence: 68%
“…3C). Quantitative measurements further showed that control optic axonal arbors had a mean branching angle of 68° (SE = 2.7, n = 91 angles in 10 control GFP arbors; also see Patel et al, 2017). However, for APCNTERM optic axonal arbors, we measured an average bifurcation angle of 75° (SE =2.9, 93 angles in 16 APCNTERM arbors).…”
Section: Apcnterm Expressing Optic Axonal Arbors Have Increased Bifurmentioning
confidence: 68%
“…In addition to our watercolour paintings, we have developed computational visualizations that mimic the temporal patterns in changes of cellular morphologies. These animations were developed using the Processing programming language (www.processing.org), based on observations of time lapse microscopic sequences of cells captured in living embryonic tissues (Patel et al, 2017). To best simulate the fractal patterns in the dynamic cell contours, we incorporated both deterministic (repetitive) and random (variable) number parameters into each of the programmes.…”
Section: Our Artwork Based On Natural Patterns In Biological Cellsmentioning
confidence: 99%
“…This leads to neurons that develop morphologies that approximate minimal spanning trees that contain a set of nodes that are branch points and/or synapse locations (Cuntz, 2012). Neurons have also inspired many artistic interpretations and visualizations (Kim, 2015;Patel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%